INTEGRASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN KESEHATAN DI ERA MODERN - Loso Judijanto; Ika Zakiah; Upus Piatun Khodijah; Al-Amin (CV. Adiba Aisha Amira, 2025)
The systematic and purposeful use of various digital technology tools, applications, and platforms to improve the eflectiveness, accessibility, and quality of education and training in the health sector, tailored to the needs and challenges of the current digital era. The research method in this study uses the literature research method. The results show that the integration of digital technology in health learning has great potential to improve the quality of education, although there are still challenges that need to be overcome. It is important to continue to conduct research and evaluation to ensure the eflectiveness and appropriateness of using technology in specific health education contexts.